2020
DOI: 10.2147/cmar.s233431
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Role of Prognostic Factors in Salivary Gland Tumors Treated by Surgery and Adjuvant Radio- or Chemoradiotherapy – A Single Institution Experience</p>

Abstract: Purpose: Salivary gland neoplasms are rare cancers of the head and neck region. Radical treatment in tumors of large salivary glands is surgery. Adjuvant treatment depends on the presence of risk factors that worsen the prognosis, but the role of these factors in patients treated by surgery with radio-or radiochemotherapy still remains unclear. The aim of the study is assessment of treatment results and identification of the risk factors affecting the prognosis in patients with tumors of large salivary glands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
1
15
1
Order By: Relevance
“…However, the positive effects of radiotherapy cannot be denied, since patients who received only radiotherapy still had a lower risk of GCD than those who did not receive either treatment (only radiotherapy vs surgery plus radiotherapy: sdHR = 1.619, 95% CI = 1.184–2.214; neither radiotherapy nor surgery vs surgery plus radiotherapy: sdHR = 3.580, 95% CI = 2.310–5.547). Almost all of the few studies of the effects of chemotherapy concluded that this treatment does not improve the survival of PGC patients, 12‐14,23,34 and we obtained the same result. However, Andry et al suggested that chemotherapy was effective in preventing the recurrence of PGC and can increase the disease‐free survival rate of patients 42 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, the positive effects of radiotherapy cannot be denied, since patients who received only radiotherapy still had a lower risk of GCD than those who did not receive either treatment (only radiotherapy vs surgery plus radiotherapy: sdHR = 1.619, 95% CI = 1.184–2.214; neither radiotherapy nor surgery vs surgery plus radiotherapy: sdHR = 3.580, 95% CI = 2.310–5.547). Almost all of the few studies of the effects of chemotherapy concluded that this treatment does not improve the survival of PGC patients, 12‐14,23,34 and we obtained the same result. However, Andry et al suggested that chemotherapy was effective in preventing the recurrence of PGC and can increase the disease‐free survival rate of patients 42 …”
Section: Discussionsupporting
confidence: 76%
“…And chemotherapy is mainly applied in the palliative setting 11 . The treatment strategy in individual patients is determined based on evaluations of the prognosis, 5,6,11‐14 and so inaccurate prognostic predictions may lead to either inadequate or excessive treatment 15 . The commonly used prognostic tool for PGC is the American Joint Committee on Cancer (AJCC) staging, which is based on the tumor size or the extent of invasion (T), nodal involvement (N), and distant metastasis (M).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of appropriate treatment has a direct impact on patient prognosis, but it is not the only prognostic factor. Findings indicate clinical factors such as histopathological type and grade of lesion, advanced tumor stage, facial nerve involvement, vascular invasion, lymph node metastasis, and distant metastasis, negatively affect prognosis [ 14 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In addition, demographic factors such as gender or age are also factors that affect prognosis [ 14 , 26 , 31 , 34 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…When treating head and neck cancers, radiotherapy is often employed, either alone or in combination with surgery [ 5 , 6 , 7 , 8 ]. In order to reduce normal tissue toxicity, the use of intensity-modulated radiotherapy has been implemented [ 9 ].…”
Section: Introductionmentioning
confidence: 99%